Dehydrogenation of Isobutane to Isobutene with Carbon Dioxide over SBA‐15‐Supported Chromia‐Ceria Catalysts. Issue 10 (7th July 2017) - Wei, Chunling; Xue, Fangqi; Miao, Changxi; Yue, Yinghong; Yang, Weimin; Hua, Weiming; Gao, Zi
Abstract : A series of SBA‐15‐supported chromia‐ceria catalysts with 3% Cr and 1%–5% Ce (3Cr‐Ce/SBA) were prepared using an incipient wetness impregnation method. The catalysts were characterized by XRD, N2 adsorption, SEM, TEM‐EDX, Raman spectroscopy, UV–vis spectroscopy, XPS and H2 ‐TPR, and their catalytic performance for isobutane dehydrogenation with CO2 was tested. The addition of ceria to SBA‐15‐supported chromia improves the dispersion of chromium species. 3Cr‐Ce/SBA catalysts are more active than SBA‐15‐supported chromia (3Cr/SBA), which is due to a higher concentration of Cr 6+ species present on the former catalysts. The 3Cr‐3Ce/SBA catalyst shows the highest activity, which gives 35.4% isobutane conversion and 89.6% isobutene selectivity at 570 °C after 10 min of the reaction. Abstract : The incorporation of ceria to SBA‐15‐supported chromia obviously improves the catalytic activity for the dehydrogenation of isobutane with CO2 due to the enhanced number of Cr 6+ species.